2019
DOI: 10.1038/s41598-019-39358-0
|View full text |Cite
|
Sign up to set email alerts
|

PLD-dependent phosphatidic acid microdomains are signaling platforms for podosome formation

Abstract: Local membrane phospholipid enrichment serves as docking platform for signaling proteins involved in many processes including cell adhesion and migration. Tissue-resident dendritic cells (DCs) assemble actomyosin-based structures called podosomes, which mediate adhesion and degradation of extracellular matrix for migration and antigen sampling. Recent evidence suggested the involvement of phospholipase D (PLD) and its product phosphatidic acid (PA) in podosome formation, but the spatiotemporal control of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…Another explanation is that other tension sensitive adaptor proteins regulate the activity or excretion of metalloproteases due to altered force distributions in podosome modules on soft substrates. We recently showed that on stiff substrates, MT1-MMP-dependent gelatin degradation is mediated by the action of phospholipase D 62 . It would be interesting to explore the role of this signaling pathway in podosome mechanosensing in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that other tension sensitive adaptor proteins regulate the activity or excretion of metalloproteases due to altered force distributions in podosome modules on soft substrates. We recently showed that on stiff substrates, MT1-MMP-dependent gelatin degradation is mediated by the action of phospholipase D 62 . It would be interesting to explore the role of this signaling pathway in podosome mechanosensing in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine phosphorylation of VEcadherin at 658 by c-Src, facilitates VE-cadherin internalization in a β-arrestin dependent manner (3), and the internalized VE-cadherin enters endosomal compartments and is either recycled to the plasma membrane or subjected to degradation (68). Recent studies have shown that spatiotemporally generated PA from PLD2 acts as signaling platforms for MT1-MMP surface trafficking and lung metastasis of breast cancer cells (69), ERK signaling in cancer cells (47), podosome formation (70), and recruitment of IQGAP1 associated with neo-intima formation (56). In addition to PLD2, PLD1 mediated PA generation in microdomains promotes vesicular fusion to the plasma membrane during exocytosis of large dense-core granules [70]; however, a role for PA confinement in microdomains in VE-cadherin redistribution to AJs is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In DCs, podosome formation is dependent on the recruitment of the Arp2/3 complex by WASp and their architecture is regulated by Cdc42, Rac, and Rho 107,135 . Using live cell imaging, recent work suggests that phosphatidic acid microdomains generated by phospholipase D drive podosome formation 136 . Podosomes are highly dynamic structures that exhibit rapid actin turnover rate as demonstrated by a fast reincorporation of GFP‐actin after photobleaching 137 .…”
Section: A Balancing Act Of Actin: Migration Versus Antigen Uptake Pmentioning
confidence: 99%
“…107,135 Using live cell imaging, recent work suggests that phosphatidic acid microdomains generated by phospholipase D drive podosome formation. 136 Podosomes are highly dynamic structures that exhibit rapid actin turnover rate as demonstrated by a fast reincorporation of GFP-actin after photobleaching. 137 The exact mechanism of how podosomes are involved in DC migration is not yet identified.…”
Section: A Balancing Act Of Actin: Migration Versus Antigen Uptake Pmentioning
confidence: 99%